Adsorption Isotherms of Glucose on Barium Sulphate Crystallites in Aqueous Positively Charged Solution at Room Temperature - Abualreish, M.J.A. (Asian Journal of Chemistry, 2010)
The adsorption isotherms of glucose on barium sulphate crystallites in aqueous positively charged solution at room temperature was investigated by spectrophotometric method. The amount of glucose adsorbed (X) increases with the increasing of the equilibrium concentrations (C) which agrees well with Freundlich-Langmuir isotherms.